2016
DOI: 10.1159/000447792
|View full text |Cite
|
Sign up to set email alerts
|

LEFTY2 Controls Migration of Human Endometrial Cancer Cells via Focal Adhesion Kinase Activity (FAK) and miRNA-200a

Abstract: Background: LEFTY2, a suppressor of cell proliferation, tumor growth, regulator of stemness and embryonic differentiation, is a negative regulator of cancer cell reprogramming. Malignant transformation may lead to migration requiring loss of adhesion and gain of migratory activity. Signaling involved in the orchestration of migration, proliferation and spreading of cells include focal adhesion kinase (FAK) and adhesion molecule E-cadherin. Aims: The present study explored whether LEFTY2 influences the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 83 publications
(38 reference statements)
2
20
0
1
Order By: Relevance
“…A previous study also clarifies that miR-29b plays a significant role in the mouse early embryonic development through modulating the expressions of DNMT3A and DNMT3B [25]. Base on the study of Alowayed et al, LEFTY2 can negatively regulate the endometrial cell proliferation and migration through inhibiting FAK activity and MKi67 expression, as well as elevating miR-200a and E-cadherin [26]. Additionally, Qiang et al have provided evidence that the down-regulation of miR-29b is one of the mechanisms underlying the excessive accumulation of the extracellular matrix, which is the most notable pathophysiological characteristic of uterine leiomyoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also clarifies that miR-29b plays a significant role in the mouse early embryonic development through modulating the expressions of DNMT3A and DNMT3B [25]. Base on the study of Alowayed et al, LEFTY2 can negatively regulate the endometrial cell proliferation and migration through inhibiting FAK activity and MKi67 expression, as well as elevating miR-200a and E-cadherin [26]. Additionally, Qiang et al have provided evidence that the down-regulation of miR-29b is one of the mechanisms underlying the excessive accumulation of the extracellular matrix, which is the most notable pathophysiological characteristic of uterine leiomyoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Regulators of actin polymerization include the focal adhesion kinase (FAK)], which activates several signaling molecules including Rac1 . Particularly, the signaling cascade activated by FAK or Rac1 further influences NHE1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have shown that LeftyA is involved in the downregulation of Na + /H + exchanger activity, reduces the resting pHi, lactate production and cell volume in Ishikawa cells [48, 49]. Interestingly, LeftyA simultaneously augments the miR-200a expression in Ishikawa cells (endometrial cancer cells) and leads to reduced migration of cells by regulating focal adhesion kinase and E-cadherin expression [50]. miR-200b could be similarly involved in maintenance of resting pHi and cell volume regulation in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%